Human Papillomavirus Vaccine Acceptance (HPV-VA) and Vaccine Uptake (HPV-VU): assessing the impact of theory, culture, and trusted sources of information in a Hispanic community - Gabriel Frietze; Margie Padilla; Jacquelin Cordero; Kristin Gosselink; Eva Moya (BMC, 2023)
Abstract Background Human papillomavirus (HPV) is the most common sexually transmitted infection and is associated with many types of cancers that disproportionately impact Hispanics. An HPV vaccine is available for individuals ages 9-45 that can prevent up to 90% of HPV-associated cancers. The current study investigates factors associated with accepting the HPV vaccine in a predominately Hispanic community. Methods A cross-sectional study design with an online questionnaire was used to collect data from a community sample of adults between the ages 18-65 residing in a U.S./Mexico border city, El Paso, Texas. Theory-based factors (e.g., the Health Belief Model), culture-based factors (e.g., familism), and trusted sources of information were examined as predictors of HPV-vaccine acceptance (HPV-VA) and HPV-vaccine uptake (HPV-VU). Results Community members (N = 602, M age = 34.65, SD = 9.79) who were predominately Hispanic (89.4%) and female (79.6%) participated in the study. Linear regression models revealed that HPV-VA was associated with household size, primary language, engagement in organizational activities, health-related community stigma, government trust, and the HBM theory-based factors: perceived benefits, perceived harm, and perceived severity. Logistic regression analyses revealed that HPV-VU was associated with household size, engagement in non-organizational activities, HPV trusted sources of information, and perceived safety. Conclusions Adequate HPV vaccination uptake among all vaccine-eligible Hispanics is an important step to lessen the HPV-attributed cancer burden. Our hypothesis that theory-based factors would be associated with HPV-VA and HPV-VU was supported. Our findings have implications for designing trusted, theory-based, and culturally sensitive health communications and interventions to promote vaccines in minority underrepresented communities.